DOUBLE SOURCE LENSING PROBING HIGH REDSHIFT COSMOLOGY - Sharma, Divij; Linder, Eric V. (Journal of Cosmology and Astroparticle Physics, 2022)
Double source lensing, with two sources lensed by the same foreground galaxy, involves the distance between each source and the lens and hence is a probe of the universe away from the observer. The double source distance ratio also reduces sensitivity to the lens model and has good complementarity with standard distance probes. We show that using this technique at high redshifts z > 1, to be enabled by data from the Euclid satellite and other surveys, can give insights on dark energy, both in terms of w0–wa and redshift binned density. We find a dark energy figure of merit of 245 from combination of 256 double source systems with moderate quality cosmic microwave background and supernova data. Using instead five redshift bins between z = 1.1–5, we could detect the dark energy density out to z ≈ 5, or make measurements ranging between 31σ and 2.5σ of its values in the bins.
Keywords: Type of access: Open Access; gravitational lensing; dark energy theory; dark energy experiments